Measurement of the antineutrino to neutrino charged-current interaction cross section ratio in MINERvA - Ren L. (2017)
We present measurements of the neutrino and antineutrino total charged-current cross sections on carbon and their ratio using the MINERvA scintillator-tracker. The measurements span the energy range 2–22 GeV and were performed using forward and reversed horn focusing modes of the Fermilab low-energy NuMI beam to obtain large neutrino and antineutrino samples. The flux is obtained using a subsample of charged-current events at low hadronic energy transfer along with precise higher energy external neutrino cross section data overlapping with our energy range between 12–22 GeV.We also report onthe antineutrino-neutrino cross section ratio, RCC, which does not rely on external normalization information. Our ratio measurement, obtained within the same experiment using the same technique, benefits from the cancellation of common sample systematic uncertainties and reaches a precision of ∼5% at low energy. Our results for the antineutrinonucleus scattering cross section and for RCC are the most precise to date in the energy range Eν < 6 GeV.